(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
During the years of transition housing stock has changed rapidly. Social changes have led to changes in the material world. The new way of life implies a different perspective on the living environment, which acquires a new appearance. It is of interest to note the dynamics of differentiation in the type and quality of housing in our country. The purpose of the present work is to determine the housing stock current state and the trends in its development.